2020
DOI: 10.1111/ans.15801
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of perianal abscess in neonates and infants

Abstract: BackgroundThe optimal management of perianal abscess in neonates and infants remains unclear, including the need for laying open of the fistula and the role of microscopy and culture studies (MCS). We aimed to report the recurrence rate following incision and drainage alone (I&D) compared to incision and drainage with laying open of the fistula (I&DF) and to determine the value of MCS in perianal abscess management.MethodsFollowing ethical approval (16326Q), a 10‐year (2007–2017) review of children you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…The rate of fistula (between the PA and the anal crypt) identified at the time of primary drainage varies widely in different studies. The percentage of communication between the PA and the internal (anal) opening was <20% (1,4,6,7,11) or more than 60% (25,27,(29)(30)(31)(32). Our results (approximately 80%) support the latter.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The rate of fistula (between the PA and the anal crypt) identified at the time of primary drainage varies widely in different studies. The percentage of communication between the PA and the internal (anal) opening was <20% (1,4,6,7,11) or more than 60% (25,27,(29)(30)(31)(32). Our results (approximately 80%) support the latter.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings are supported by several studies. There were no recurrences (26,27,31) or the recurrence rate was <15% (29,30,32) in patients who underwent fistulotomy at the time of ID. These findings are in excellent agreement with ours.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A recent study also showed that the recurrence rates of incision drainage and fistulotomy were 34.6% and 15.3%, respectively, and the difference was significant (P = .04). 35 However, some studies have reported that after fistulectomy in adults, the recurrence rate of anal fistula is 16%-70%, and the incontinence rate is between 0% and 40%. 36 Compared with adults, infantile fistula is lower in position, shorter in length, and involves less of the sphincter, which can be easily found during the operation.…”
Section: Surgical Treatmentmentioning
confidence: 99%